Design and Control Method for Compact BOP of Direct Methanol Fuel Cell - Chang, Y. -S.; Cho, C.; Kim, Y. (PROTON EXCHANGE MEMBRANE FUEL CELLS 8, PTS 1 AND 2, 2008)
We have developed an electro-chemical model of a DMFC (Direct methanol fuel cell) stack to analyze its performance. The model includes methanol solution at the anode to "cross over" to the cathode through MEA (membrane electrode assembly), which reduces the system efficiency and increases fuel consumption. BOP (Balance of plants) system - condenser, cooler, and methanol solution tank - was modeled. Dynamic simulation was performed to evaluate and develop a control algorithm of the fuel cell system for an efficient operation of DMFC. We simulated the effects of the varying total UA (overall heat transfer coefficient), and proposed minimum UA of the condenser and cooler. When the volume of the methanol solution tank decreases below a certain level, ON/OFF based control algorithm leads to an unstable fuel cell operation. By adopting PID based control algorithm, the system has better controllability of methanol concentration and power generation in response to load change under the same methanol solution tank volume.